1989
DOI: 10.1128/mcb.9.11.5260
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by phospholipids of the interaction between R-ras, rho, and their GTPase-activating proteins.

Abstract: Certain lipids were found to inhibit the interaction between rho and R-ras proteins and their respective GTPase-activating proteins (GAP). Inhibitory lipids were similar for each protein but differed significantly from those previously found to inhibit the interaction between ras protein and GAP activity. These data raise the possibility that ras and related proteins are controlled biologically by interactions between lipids and GAP molecules.R-ras and rho are related to the proto-oncogene ras by sequence homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 18 publications
(18 reference statements)
3
32
0
Order By: Relevance
“…One reported effect of PDGF and other growth factors is activation of ras-GTP (Gibbs et al, 1990;Satoh et al, 1990), which then initiates either cell division through activation of raf (Moodie et al, 1993) or chemotaxis through activation of rac and rho (as seen by increased actin polymerization, focal adhesions and stress fibers) . LPA can also induce activation of the (Tsai et al, 1989). The ability of both LPA and PDGF to induce/3-actin mRNA localization, suggests that this localization may possibly be through the and rac as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One reported effect of PDGF and other growth factors is activation of ras-GTP (Gibbs et al, 1990;Satoh et al, 1990), which then initiates either cell division through activation of raf (Moodie et al, 1993) or chemotaxis through activation of rac and rho (as seen by increased actin polymerization, focal adhesions and stress fibers) . LPA can also induce activation of the (Tsai et al, 1989). The ability of both LPA and PDGF to induce/3-actin mRNA localization, suggests that this localization may possibly be through the and rac as well.…”
Section: Discussionmentioning
confidence: 99%
“…LPA is a potent stimulator of platelet aggregation which has been shown to activate the rho-class of GTPases (Tsai et al, 1989;. Addition of LPA to serum-starved CEFs resuited in a significant increase in ceils exhibiting peripheral ~-actin mRNA (Fig.…”
Section: Serum Pdgf and Lpa Induce ~-Actin Mrna Localizationmentioning
confidence: 99%
“…GTPase-activating-protein-(GAP)-induced stimulation of ras-p21 GTPase activity was assayed as previously described [23]. ras-p21 (kindly donated by Dr A.…”
Section: Gtpase-activating Protein Activitymentioning
confidence: 99%
“…In addition, several small GTP binding proteins such as Rac and Cdc42 Coso et al, 1995;Minden et al, 1995) and protein tyrosine kinases such as Pyk2 and Vav Tokiwa et al, 1996) have been reported to stimulate JNK/SAPK pathway and lie upstream to the MEKK1. In fact, earlier studies have demonstrated that arachidonic acid and its LOX metabolites, HETEs, activate these GTP binding proteins by inhibiting the activity of their respective GTPase activating proteins (GAPs) (Han et al, 1991;Yu et al, 1990;Tsai et al, 1988Tsai et al, , 1989. Because arachidonic acid and its LOX metabolites possess the ability to activate GTP-binding proteins such as Rac, it is likely that these proteins play a role in the activation of JNK1 by these lipid molecules.…”
mentioning
confidence: 99%